THE The Effect of Extensive Reading Strategy on Students’ Reading Comprehension at Smp Dharma Wanita In The Academic Year Of 2023/2024 - Prayuda, Meikardo Samuel; Ginting, Fiber Yun A; Dila Afrilia (English Language Education Department, Universitas Majalengka, 2023)
The objectives of this study is to find out whether extensive reading give significant effect to the students’ reading comprehension. The method in this research was Experimental research. This research had been conducted at SMP Dharma Wanita. The Population of this research was the eighth grade students of SMP Dharma Wanita which consisted of 48 students into two classes, namely VIII-A and VIII-B. VIII-A as the experimental class and VIII-B as the control class. Both of classes consisted of 48 students with homogenous score. The experimental class treated by using extensive reading strategy, while the control class was using the conventional ways. The pre-test was given to the two groups before giving the treatment. The result of pre-test showed the mean score of experimental class was 40,16 and the control class was 36,35. After giving the treatment, post-test was given. The result of post-test showed the mean score of experimental class was 72,64 and the control class was 39,65. The value of t-test was higher than the ratio on t-table (11,424>1,678). Therefore, Ho was rejected and Ha was accepted. In conclusion, Extensive Reading Strategy can be effectively to be used to teach reading comprehension of eighth grade students of SMP Dharma Wanita.